2019
DOI: 10.14744/bej.2019.49469
|View full text |Cite
|
Sign up to set email alerts
|

Progression Analysis With ABCD Grading System Following Corneal Collagen Cross-Linking in Keratoconus

Abstract: To evaluate the ABCD grading system used in follow-up of keratoconus progression after the corneal collagen cross-linking (CXL) treatment in different Kmax groups. Methods: This study included 57 eyes of 43 patients applied with CXL treatment for progressive keratoconus. All the patients were applied with the standard CXL protocol (Dresden). According to the changes in the Kmax value at the end of 12 months postoperatively (0-1D, 1-2D, >2D), the groups were separated as steepening and flattening. Scheimpflug p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…Saglik et al found a regression in parameter A in the one-year post-standard procedure follow-up, as in the CXL30 group in the present study. Other parameters showed similar trends to the current study [ 39 ]. However, they found a significant positive correlation between the change in Kmax values and parameter A.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Saglik et al found a regression in parameter A in the one-year post-standard procedure follow-up, as in the CXL30 group in the present study. Other parameters showed similar trends to the current study [ 39 ]. However, they found a significant positive correlation between the change in Kmax values and parameter A.…”
Section: Discussionsupporting
confidence: 89%
“…In the literature, only a few studies evaluated the applicability of the ABCD staging system in monitoring the efficacy of the standard procedure. In contrast, only one recently published retrospective study investigated its utility in evaluating accelerated protocols and compared the effectiveness of different protocols regarding the ABCD grading system [ 8 , 39 , 40 , 41 , 42 , 43 ]. Danesh and coauthors showed no significant changes in parameters A and D, while parameters B and C significantly increased one year after conventional CXL [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sağlık et al . [ 21 ] showed significant regression in parameter A 1 year after CXL, which coincides with the results of Bardan,[ 16 ] but differs from the results of the current study. Bardan et al .…”
Section: Discussionsupporting
confidence: 67%
“…The flattening of Kmax, which was shown in many previous studies, was not noticed in ours, although it should be emphasized that the values of Kmax remained stable over time. [ 16 21 23 ]…”
Section: Discussionmentioning
confidence: 99%
“…There have been many reports of increased posterior elevation after CXL. 27 , 29 It is suggested that posterior steepening along with anterior flattening may be the cause for the stabilisation of keratometric values after CXL. 29 Other study found no significant changes in posterior elevation after CXL.…”
Section: Discussionmentioning
confidence: 99%